The Effect of Liquidity, Leverage, Profitability, and Company Size on Corporate Taxes: Especially in Coal Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange 2018-2020 - Agus Romdoni; Pandoyo (CV ODIS, 2022)
This study aims to provide evidence regarding the effect of liquidity, leverage, profitability, and firm size on the company's ability to pay taxes. The sampling method used in this study was purposive sampling, while the statistical methods used in this study were simple regression and multiple regression. The number of samples taken are 10 coal sub-sector mining companies listed on the IDX from 2018-2020. The data is processed using SPSS 22. The results showed that the coefficients of liquidity (CR) and profitability (ROE) were 0.142 and 0.380. This means that liquidity and profitability have a positive and insignificant effect on income tax. Leverage (DER) and firm size, which have a positive and significant effect on income tax, the coefficient values are 0.616 and 71.28